Asociación entre ferropenia sin anemia y trastornos menores de salud en adolescentes universitarias: Association between ferropenia without anemia and minor health disorders in university adolescents - Guevara Maticorena, Brenda (2022)
Abstract Iron deficiency o “ferropenia” represents the most prevalent nutritional deficiency in the whole world and its refers to the insufficient presence of iron in the organism; this review is to delve more about iron deficiency so that we can diagnose this deficiency in its first stages, emphasizing various minor disorders that could guide our diagnosis. Methods: searches included articles in Spanish and English, about this topic. The search engines included are Google Scholar, ScienceDirect – Elsevier library, PubMed, SciELO. Results: based in only 9 of the articles, it was found that the prevalence of ferropenia is even greater than iron deficiency anemia, as well as that it had a clear impact at the cognitive level, being more remarkable in females, who represents a risk group. Conclusions: the impact at the multi system level in the organism that can cause socio – economic problems in different countries are the cognitive impairment, preventing optimal development of the person, so that we have to solve this problem from the beginning. Key words: iron deficiency, serum ferritin, anemia, iron deficiency anemia, neurological symptoms. DOI: https://doi.org/10.25176/RFMH.v18.n1.1276